2001
DOI: 10.1034/j.1600-6143.2001.001003228.x
|View full text |Cite
|
Sign up to set email alerts
|

Indirect Allorecognition of Mismatched Donor HLA Class II Peptides in Lung Transplant Recipients with Bronchiolitis Obliterans Syndrome

Abstract: A correlation between indirect allorecognition of mismatched donor HLA class I peptides and development of bronchiolitis obliterans syndrome (BOS) after lung transplantation has been previously observed. The aim of this study was to determine whether there was a correlation between indirect allorecognition of mismatched donor HLA class II peptides and development of BOS after lung transplantation. Peripheral blood mononuclear cells from nine BOSπ and nine BOSlung transplant recipients were cultured with synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
70
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 47 publications
5
70
0
Order By: Relevance
“…Although the exact role of CD30 in the pathogenesis of BOS is unknown, alloimmune response is considered as a major contributor in the immuno-pathogenesis of BOS (5,16,17). We have shown that BOS+ patients develop early post-transplant inflammation which may activate allo-as well as auto-immunity (18).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Although the exact role of CD30 in the pathogenesis of BOS is unknown, alloimmune response is considered as a major contributor in the immuno-pathogenesis of BOS (5,16,17). We have shown that BOS+ patients develop early post-transplant inflammation which may activate allo-as well as auto-immunity (18).…”
Section: Discussionmentioning
confidence: 90%
“…BOS is histologically characterized by cellular infiltration, fibrosis, collagen deposition and occlusion of small airways in the allograft (4). The role of T cell immunity in the pathogenesis of chronic lung allograft rejection both in clinical lung transplantation and in animal models of obliterative airway diseases has been well established (5,6). Therefore, it is reasonable to predict that sCD30 which is a marker for T cell activation may increase during rejection of the allograft.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53][54] Nonetheless, a gap exists between our understanding of how T cells are activated through the indirect pathway and how such activated T cells predominantly induce chronic pathology. The results presented in this report provide a potential explanation to bridge this gap.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, one important point is that over time after organ transplantation, T cells may recognize different epitopes of donor antigens in the same individuals, a process called epitope spreading. This phenomenon has been described in renal (39), cardiac (40), and lung transplant recipients (41). This process has been implicated as a mechanism for continual recruitment of naïve alloreactive T cells, which may contribute toward acute and chronic rejection.…”
Section: Antigen-specific Assays For Monitoring Transplantation Immunmentioning
confidence: 94%